Supporting the Running and Analysis of Trials of Web-Based Behavioural Interventions: The LifeGuide. - Yang, Y; Osmond, A; Chen, X; Weal, M; Wills, G; Roure, D; Joseph, J; Yardley, L (IEEE, 2009)
Behavioural interventions - packages of advice and support for behaviour change - are one of the most important methodologies and technologies employed by social scientists for understanding and changing behaviour. A typical web-based behavioural intervention study includes the designing, deploying, piloting and trialling of the intervention as well as data analysis. We have developed a research environment named LifeGuide, which covers the full scope of this process, enabling social scientists to carry out intervention studies with minimal technical expertise. In this paper, we present how the LifeGuide can assist and accelerate intervention research, particularly focusing on supporting the running and analysis of trials of web-based behavioural interventions along with the case study of an intervention that has been developed within the LifeGuide. © 2009 Crown Copyright.